(untitled) (World Economics and Finance Bulletin, 2023)
The study aims to demonstrate the relationship of liability accounting in cost reduction with performance evaluation, and the use of cost on the basis of liability accounting Centers , for the effectiveness of planning ,control, performance evaluation and cost reduction in the Iraqi Khazer company, and work on the types of responsibility centers in it . The researcher used the method of analysis, and the sample of the study was represented by Al-Khazer company, an industrial company, interested in the trade of building materials, real estate investments and general contracting, one of the formations of the Iraqi Ministry of industry and minerals, with time limits set for the year 2021, where the problem of the study was posed by the following question: "How is accounting based on And what is its role in reducing costs " after delving into the details of the theoretical and practical study of it, the researcher concluded that evaluating performance according to the Centers of responsibility, represents the line of Defense for the company’s survival in the market, and raises the competitiveness of its products , by linking each center of responsibility with a specialist manager, the results indicate , We note that there is a reduction in costs in some centers ,and this indicates that the company is aware of the risks assigned to it , and is working to rationalize costs for the better , and the researcher recommends that the company’s performance should be divided into more responsibility centers ,linking each responsibility center with its own manager , and shouldering all responsibility towards improving performance and reducing competitive position based on performance.